2012
DOI: 10.1039/c2dt30553d
|View full text |Cite
|
Sign up to set email alerts
|

A very simple method to synthesize nano-sized manganese oxide: an efficient catalyst for water oxidation and epoxidation of olefins

Abstract: Nano-sized particles of manganese oxides have been prepared by a very simple and cheap process using a decomposing aqueous solution of manganese nitrate at 100 °C. Scanning electron microscopy, transmission electron microscopy and X-ray diffraction spectrometry have been used to characterize the phase and the morphology of the manganese oxide. The nano-sized manganese oxide shows efficient catalytic activity toward water oxidation and the epoxidation of olefins in the presence of cerium(IV) ammonium nitrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 72 publications
1
52
0
Order By: Relevance
“…The oxygen evolution rate increases with increasing concentration of Ce(IV). The increase in the oxygen evolution rate in low concentration of Ce(IV) is fast in the Ce(IV) concentration range of 0.01 -0.1 M. However, in higher concentrations of Ce(IV), the slope of the increasing the oxygen evolution rate is slow (is less steep) [65].…”
Section: A Very Simple Methods To Synthesize Nano-sized Manganese (Iiimentioning
confidence: 91%
See 3 more Smart Citations
“…The oxygen evolution rate increases with increasing concentration of Ce(IV). The increase in the oxygen evolution rate in low concentration of Ce(IV) is fast in the Ce(IV) concentration range of 0.01 -0.1 M. However, in higher concentrations of Ce(IV), the slope of the increasing the oxygen evolution rate is slow (is less steep) [65].…”
Section: A Very Simple Methods To Synthesize Nano-sized Manganese (Iiimentioning
confidence: 91%
“…The nano-sized manganese (III) oxide also showed a high activity in epoxidation of aromatic olefins and a mild activity in the epoxidation of some non-aromatic olefins in the presence of H 2 O 2 and bicarbonate ion [65].…”
Section: A Very Simple Methods To Synthesize Nano-sized Manganese (Iiimentioning
confidence: 99%
See 2 more Smart Citations
“…MnO x nanocomposites have attracted increasing attention in photocatalysis, energy storage, and Li ion batteries because of their low cost, environmental abundance, and high theoretical specific capacitances. 4,5 Recently, several research groups have reported that graphene-supported MnO x nanocomposites can play a critical role in energy storage [5][6][7] and can be prepared by using an aqueous chemical method, 8 chemical reduction, [9][10][11] and colloidal mixing. 12 However, these methods are somewhat complicated and require different synthetic protocols to prepare specific MnO x nanoparticles (NPs) on graphene, which makes it difficult to produce those nanocomposites.…”
Section: -3mentioning
confidence: 99%